(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Two cases of the rare blood group Bombay phenotype are discussed here. This rare blood group, Bombay (Oh) was first established by Bhende et al in Bombay (Mumbai), in 1952.In the ABO (ABH) blood group system, the O antigen represents the lack of A or B antigens; however it has the most amount of H antigen. If the H gene is absent, which is extremely rare, H substance can not be formed and subsequent A and B antigens can not also be formed. Absence of H gene results in the Bombay phenotype (Oh) 1-6, 7-13. Individuals with the Bombay phenotype develop anti-H antibodies. This is the reason that undetected Bombay individuals (typically typed as O individuals) will be cross match incompatible with O individuals. Bombay phenotype individuals can only receive blood from other Bombay individuals. In India, 1 in 10,000 has been found to have Bombay blood group. Where as, in Bangladesh till now only nine persons with Bombay (Oh) blood group have been formally reported by the Transfusion Medicine Department of Bangabandhu Sheikh Mujib Medical University (BSMMU). Using two cases we would like to discuss strategies to properly diagnose cases of Bombay phenotype in Bangladesh DOI: http://dx.doi.org/10.3329/jbcps.v29i4.11347 J Bangladesh Coll Phys Surg 2011; 29: 241-243